Effect of replacing black soldier fly larvae powder with soybean meal in the ration on some egg quality traits in laying hens - Zaki, Ali N.; Naji, Saad A. (Journal of Kerbala for Agricultural Sciences, 2022)
This experiment was conducted in a private farm (Al-Amer Poultry Company) in Al-Mahawil District of Babil Governorate for the period from 29-9-2020 to 18-1-2021 (16 weeks) to investigate the effect of Replacing Black Soldier Fly Larvae Powder With Soybean Meal in the Ration on some egg quality traits in laying hens by using 60 Lohmann brown hens, 55 weeks of age. Birds were randomly assigned to five treatments, 16 hens per treatment, and each treatment constituted of four replicates, with 4 hens per replicate. The experiment’s treatments were as follows: (T1): control, (T2): BSF larval meal was partially replaced by 25% in the place of Soybean meal, (T3): BSF larval meal was partially replaced by 50% in the place of Soybean meal, (T4): Partially replace 75% BSF larval powder in soybean meal, (T5): completely replace 100% BSF larvae powder. The results indicated that the replacement of soybean meal by larvae BSF produce a significant improvement during the total period (56–71 weeks) of the experiment in: shell thickness, shell weight, shell weight relative, albumen weight relative, albumen height, yolk weight, yolk weight relative, yolk height, and yolk index. It is concluded from the experiment that replacing black soldier fly larvae powder with soybean meal led to an improvement in some qualitative characteristics of eggs produced from these hens. Thus, BSF larvae can be used as a successful and economical alternative in laying hens diets to improve some egg quality characteristics.